2020
DOI: 10.1063/1.5143839
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation, thermoelectric properties, and crystal structure of boron-doped Mg2Si single crystals

Abstract: Mg2Si is a potential thermoelectric (TE) material that can directly convert waste energy into electricity. In expectation of improving its TE performance by increasing electron carrier concentration, the element boron (B) is doped in Mg2Si single crystals (SCs). Their detailed crystal structures are definitely determined by using white neutron holography and single-crystal x-ray diffraction (SC-XRD) measurements. The white neutron holography measurement proves that the doped B atom successfully substitutes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 44 publications
2
36
1
Order By: Relevance
“…Comparison of the atomic image with the expected location of Sn and interstitial atoms did not give a reasonable result, similar to the case of the Bdoped Mg 2 Si SC. 26 In other words, the B dopant substituted for the Mg site. It should be noted that the third-nearest Mg atoms were clearly observed relative to the firstand secondnearest ones in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparison of the atomic image with the expected location of Sn and interstitial atoms did not give a reasonable result, similar to the case of the Bdoped Mg 2 Si SC. 26 In other words, the B dopant substituted for the Mg site. It should be noted that the third-nearest Mg atoms were clearly observed relative to the firstand secondnearest ones in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the fact that the B-doping to the Mg 2 Si SC induced V Si , 26 it is concluded that the B-doping has the effect of generating vacancy defects in the Mg 2 Sn and Mg 2 Si SCs owing to the increased chemical pressure. It should be noted that the V Mg fraction of the B-doped Mg 2 Sn SCs is much higher than the V Si fraction of the B-doped Mg 2 Si SCs (e.g., 2.1(14)% at x = 0.75% 26 ). The high V Mg fraction could be one reason why the disorder was only observed in the Mg atoms in the B-doped Mg 2 Sn SC presented in Figure 1a.…”
Section: Sc-xrdmentioning
confidence: 99%
See 3 more Smart Citations